Education Quality Management in Improving Junior High School Performance in Tangerang Regency - Jamalus; Sutaryat Trisnamansyah; Supyan Sauri; Yosa Iriantara (International Journal of Science Education and Technology Management, 2023)
The background of this research is that the quality of junior high school graduates in Tangerang Regency is still low. This is due to SMP management that has not been optimal both in terms of organizational planning, program implementation, evaluation and problem solutions. The purpose of this study was to find out the activities carried out in planning, organizing, assessing junior high schools in Tangerang Regency, the obstacles encountered and solutions to overcome the obstacles. This study uses a qualitative approach based on the results of observations, interviews and documentation. This study uses the main theory, namely the management theory of Terry. The results of the study show: 1) Planning Has been carried out oriented to the guidelines, but not all aspects that should exist in the planning function have been carried out, an important problem that has not been carried out is the identification of performance improvement problems that have not touched the problems faced by teachers in improving their performance..2) In Quality implementation is carried out oriented to guidelines for improving the performance of junior high school teachers; 3) In Evaluation is carried out oriented to the management supervision function, however, not all aspects of supervision have been carried out, there is no supervision of supervisors from senior teachers and supervision is still not optimal in following up on the results of supervision 4) The obstacle encountered is the 3M factor, namely the Man factor (supervisor and supervisor). teachers), Materials (infrastructure) and Money (budget / financing), the Man factor is still the main constraint factor in the implementation of improving the performance of SMP; 5) The solution, to overcome the problem is to overcome the constraints of limited facilities and budget factors, the supervisors and principals of junior high schools make a more precise budget preparation and make budget efficiency for the school operational financing component.